Optimization and characterization of nanoemulsion containing aripiprazole and its toxicity on zebrafish - Samiun, Wan Sarah (2019)
Poorly water soluble drugs have been a major problem in the development of drug formulation. Thus, the main aim of this study is to optimize the composition of formulation and the preparation conditions of nanoemulsion containing aripiprazole which is a poorly water-soluble drug. In the optimization study, Mixture Experimental Design (MED) and Artificial Neural Networks (ANNs) were carried out to formulate nanoemulsion compounds containing aripiprazole by varying five components of mixture composition. Estimation of particle size of nanoemulsion containing aripiprazole by MED and ANN were 64.24 nm and 64.38 nm, respectively. The results showed that MED model predicted is more accurate as compared to ANN since MED model has a lower percentage of RSE (2.01%). The optimum compositions of the model were 3.00% of palm kernel oil ester (PKOE), 2.00% of lecithin, 1.00% of Tween 80, 2.25% of glycerol and 91.75% of deionized water. Response Surface Methodology (RSM) was used to optimize the process parameter conditions in preparation of the optimum nanoemulsion formulation. This design was used to study the effects of four independent variables: the stirring time, shear rate, shear time, and the number of cycle of high-pressure homogenizer with the function of particle size as the response. The optimum process parameter conditions obtained were 120 min of stirring time, 15 min of shear time, 4400 rpm of shear rate and 11 cycles of high pressure homogenizer. By using RSM, the experimental value of the particle size was 64.52 nm which was very close to the predicted value (62.59 nm) with 1.93% of RSE value. The physicochemical properties of optimized nanoemulsions revealed the particle size of 62.23 nm, polydispersity index (PDI) of 0.18, zeta potential of - 31.6 mV, pH of 7.45, viscosity of 3.72 cps and osmolality of 297 mOsm/kg, suggesting their compatibility for parenteral administration. Aripiprazole was incorporated into nanoemulsion system with an entrapment efficiency of 97.3% and a relatively high drug loading of 93.14%. The optimized formulation demonstrated sufficient physical stability upon long-term storage at 4 °C, 25 °C and 45 °C. The ability of nanoemulsion to deliver aripiprazole through was assessed in vitro using Franz diffusion cell and showed the permeability of aripiprazole was significantly increased from 2.22% at 1 h to 93.06% after 24 h drug release. In the toxicity study, the toxic effect of nanoemulsion containing aripiprazole, blank nanoemulsion and aripiprazole were tested by using zebrafish embryos and larvae (Danio rerio) during 120 hours post exposure. From this assessment, aripiprazole showed LC50 value of 473.7 μg/mL towards zebrafish embryos. Nanoemulsion containing aripiprazole and blank nanoemulsion showed LC50 value of 140.2 μg/mL and 78.21 μg/mL towards zebrafish embryos, respectively. However, during the developmental toxicity, all the survived zebrafish larvae showed severe toxicity effect at high concentration of samples more than 250 μg/mL such as chronic pericardial edema, bradycardia, scoliosis and non-detachment of tail. Regardless of the presence of surfactant toxic effect, surfactant must be chosen wisely within the optimum concentration in producing formulation nanoemulsion.